2014
DOI: 10.1037/a0036735
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities for psychologists in palliative care: Working with patients and families across the disease continuum.

Abstract: Interdisciplinary palliative care services have been rapidly expanding in health care settings over the past 10 years, particularly through the establishment of interdisciplinary palliative care teams. Relatively few of these teams formally include psychologists, although their skills of enhancing patients' and families' well-being and lessening suffering make an enormous contribution to the care provided. In this article, we define palliative care in broad terms, distinguishing it from hospice and end-of-life… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
40
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 109 publications
(123 reference statements)
0
40
0
Order By: Relevance
“…Major distress in any of these areas can result in depression, anxiety, and suicidality (Boston et al, 2011), and psychological distress is often reported as being more significant to a person's quality of life during terminal illness than physical pain and physical symptom relief (Robbins, Simmons, Bremer, Walsh, & Fischer, 2001). As such, psychologists have the potential to make a vital contribution to alleviate end-of-life suffering (Kasl-Godley, King, & Quill, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Major distress in any of these areas can result in depression, anxiety, and suicidality (Boston et al, 2011), and psychological distress is often reported as being more significant to a person's quality of life during terminal illness than physical pain and physical symptom relief (Robbins, Simmons, Bremer, Walsh, & Fischer, 2001). As such, psychologists have the potential to make a vital contribution to alleviate end-of-life suffering (Kasl-Godley, King, & Quill, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…SS4WB offers participants meaning through enjoyment, personalised activity and social engagement. Additionally, taking part in the workshops decreases social isolation (Kasl-Godley et al, 2014). Just "getting out and about and doing something"…”
Section: Discussionmentioning
confidence: 99%
“…End‐of‐life care has traditionally been seen as the territory of physicians, nurses, social workers, and clergy, despite the key contributions psychology may offer (Kasl‐Godley, King, & Quill, ). As such, the role of psychologists within this area of healthcare is still developing.…”
mentioning
confidence: 99%
“…Haley, Larson, Kasl‐Godley, Neimeyer, and Kwilosz () identified training needs as a key challenge, in that end‐of‐life care is not seen as a priority area within psychological university curricula and post‐university professional development in the same way as it is for other disciplines such as medicine and nursing. Kasl‐Godley et al () proposed a call for action and in so doing, articulated several knowledge areas with which psychologists should familiarise themselves in order to contribute effectively in end‐of‐life care: Biological aspects of illness and the dying process; Psychological, sociocultural, spiritual, and interpersonal factors in chronic, advanced, life‐limiting, and terminal illness; Normal and abnormal grief and bereavement; Communication and facilitation of advance care planning; Assessment of common physical and mental health conditions; Psychotherapy for patients with chronic, life‐threatening, or terminal illness; Assessment and treatment of families; and Interdisciplinary teams, consultation, and professional self‐care. …”
mentioning
confidence: 99%